Peran Konselor Sekolah Dalam Membantu Siswa Menentukan Pilihan Studi Lanjut - Nidaurrohmah (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the role of school counselors in helping students determine their further education choices and the factors influencing their decisions. The research method used is a mixed-methods approach with a descriptive design, combining quantitative data through questionnaires and qualitative data through in-depth interviews. The research sample consists of 100 students and 10 school counselors from several high schools. The findings show that school counselors play a crucial role in providing clear information about further study options and supporting students in overcoming social pressure and anxiety that arise during the decision-making process. The majority of students feel more confident and have a better understanding after participating in counseling sessions. However, challenges related to time and resource limitations hinder the ability to provide more in-depth guidance. This study suggests the need for additional support from schools and the government to enhance counselors' capacity to effectively assist students in planning their futures. Overall, school counselors play a vital role in guiding students toward better decisions regarding higher education and their careers.